2006
DOI: 10.1038/modpathol.3800647
|View full text |Cite
|
Sign up to set email alerts
|

Positive immunohistochemical staining of KIT in solid-pseudopapillary neoplasms of the pancreas is not associated with KIT/PDGFRA mutations

Abstract: Solid-pseudopapillary neoplasms of the pancreas are uncommon neoplasms of low malignant potential and of uncertain histogenesis. A small percentage of patients develop metastatic disease and some succumb to disease. The management of patients with metastatic disease or unresectable tumor, and patients who are just not good surgical candidates is problematic. Novel therapy targets are needed. Successful treatment of metastatic and unresectable gastrointestinal stromal tumors with KIT kinase inhibitor, imatinib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 38 publications
1
21
0
2
Order By: Relevance
“…7,8 Recently, we showed that solid pseudopapillary neoplasms express FLI-1, which has also been demonstrated in neuroendocrine tumors of the skin (so-called Merkel cell carcinomas). 9 Finally, a non-mutation-mediated activation of c-kit was demonstrated in about 50% of solid pseudopapillary neoplasms, 10 a finding similar to that seen in neuroendocrine small cell carcinomas of the lung. 11,12 When the genes encoding for the above mentioned markers are localized, it is striking that many of them reside on chromosome 11q, a chromosomal area that also is involved in the genetics of pancreatic neuroendocrine tumors because it harbors the MEN1 gene.…”
mentioning
confidence: 61%
“…7,8 Recently, we showed that solid pseudopapillary neoplasms express FLI-1, which has also been demonstrated in neuroendocrine tumors of the skin (so-called Merkel cell carcinomas). 9 Finally, a non-mutation-mediated activation of c-kit was demonstrated in about 50% of solid pseudopapillary neoplasms, 10 a finding similar to that seen in neuroendocrine small cell carcinomas of the lung. 11,12 When the genes encoding for the above mentioned markers are localized, it is striking that many of them reside on chromosome 11q, a chromosomal area that also is involved in the genetics of pancreatic neuroendocrine tumors because it harbors the MEN1 gene.…”
mentioning
confidence: 61%
“…23 Also, studies have reported that B50% of solid-pseudopapillary neoplasms express KIT, a well-known stem cell marker. 24 Interestingly, examination of stem cell marker expression in our microarray data did not reveal any significant changes in these markers in solid-pseudopapillary neoplasms (Supplementary Table 2). Instead, the expression of genes associated with epithelial-mesenchymal transition changed dramatically in solid-pseudopapillary neoplasms.…”
Section: Expression Of Tumor Differentiation Markersmentioning
confidence: 78%
“…34 We conclude from our data that in Merkel cell carcinoma, expression of KIT and occurrences of activating mutations in the receptor may be unrelated events. This is true in other tumors as well, such as solid psuedopapillary neoplasms of the pancreas, 35 melanomas, 36,37 pulmonary small cell carcinomas 38,39 and breast carcinomas. 40 Cytogenetic studies revealed frequent genetic abnormalities in Merkel cell carcinoma, 5 but no alterations were observed in chromosome 4q12, the area to which KIT and PDGFRA are mapped.…”
Section: Discussionmentioning
confidence: 91%